Creating your digital design portfolio : a practical guide to showcasing your work online - Clazie, Ian. (Switzerland : RotoVision, 2010)
This is a comprehensive manual. It equips designers and illustrators with all they need to know to build and present a digital portfolio that packs a punch and will stand out in today's competitive creative job market.
Keywords: Art portfolios -- Design; Design services -- Marketing; Computer graphics; Graphic arts -- Vocational guidance